TINJAUAN FIQIH EKONOMI TERHADAP JUAL BELI PESANAN BARANG RUMAH TANGGA DI NAGARI TUNGKAR KECAMATAN SIMONA KABUPATEN LIMA PULUH KOTA - Vicky Azhari; Zainuddin (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2021)
This article examines the economics viewpoint of buying and selling goods ordered by household by order in Nagari Tungkar, Lima Puluh Kota Regency. The problem is the mismatch between the goods ordered and the original request from the buyer in buying and selling orders. However, because the goods have arrived at the place of the orderer, he must accept them for various reasons even though they are not in accordance with his wishes. This research is a field research with a descriptive qualitative approach. The data sources in this study are housewives who purchase household goods by order and sellers of goods. Based on the results of the research, according to the economics science review of the sale and purchase of household goods by order carried out by housewives in Nagari Tungkar, Simona District, Fifty cities in accordance with the principles of Economic Fiqh. As for the inadequacy of the goods and the order, there is a communication error between the seller and the buyer. The seller does not accept the return of the goods because there is an initial agreement with the buyer, while the seller has spent a lot of money in the process of making the goods. The seller and the buyer have agreed in advance on the terms promised at the beginning of the contract and the sale and purchase is valid according to Economic Fiqh.